Pengaruh Gaya Kepemimpinan Situasional, Budaya Organisasi Dan Kompensasi Terhadap Kinerja - P. Hellen Wijaya; Christina Catur Widayati; Chichi Rahmayanti (Jurnal Ekonomi, 2018)
This research aims to examine and analyze the influence of situational leadership style, organizational culture and compensation on the performance of employees. The methods used in this research is descriptive method. The object of this research is all staff office division who worked in PT. CIMB NIAGA Kuningan Plaza Branch Office with a population 75 people. The sampling using the method of population (census) is to examine the entire population. The approach used in this research is a Structural Equation Models (SEM) with Smart analysis tools-PLS.The results showed situational leadership style gives a positive and significant influence on employee performance.organizational culture gives a positive and significant influence on employee performance. Compensation provides a positive and significant effect on performance employees. This is evidenced from the results of hypothesis testing (t-test) which shows the significance value of the independent variables.